La depresión infantil en niños de 6 a 12 años - Hoyos, Lucía
The student depression in the children from 6 to 12 years: causes and boarding process. In the present job of investigation, we pretend to realize a theoretical boarding about the theme of the childhood depression, it will analyze the different theories that have treated the theme, the historical evolution that has had until being considered as a sickness that also affects the children. It will try to analyze which are the main causes that unchain the depression, how to do to diagnose on time, to treat them opportunity. With this job, we pretend to wake up the interest as in the parents as in the teachers to analyze their attention and realize how much we can affect our children in the emotional environment, doing in that way to get down the children´s autoestima to take them to depressive stages. Finally we will find in this job some tests to be applied to diagnose the depressive problems in the boy or girl. En el presente trabajo investigativo se espera realizar un abordaje teórico sobre el tema de la depresión infantil, se analizarán las diferentes teorías que han tratado el tema, la evolución histórica que ha tenido hasta ser considerada como una enfermedad que afecta también a los niños.Se tratará de analizar cuáles son las principales causas que desencadenan la depresión, cómo hacer para poderlas diagnosticar a tiempo, para poder tratarlas oportunamente. Finalmente encontraremos en este trabajo algunos de los test que se pueden aplicar para diagnosticar problemas depresivos en el niño-a.